2021
DOI: 10.1002/ange.202016332
|View full text |Cite
|
Sign up to set email alerts
|

Hidden Mechanism Behind the Roughness‐Enhanced Selectivity of Carbon Monoxide Electrocatalytic Reduction

Abstract: High roughness has been proved to be an effective design strategy for electrocatalyst in many systems. Especially, high selectivity of carbon monoxide reduction (CORR) in competition with the hydrogen evolution reaction has been observed on high roughness electrocatalysts. However, the two well-known mechanisms, i.e., decreasing the energy barrier of CORR and increasing local pH, failed to understand the roughness-enhanced selectivity in a recent experiment. Herein we unravel the hidden mechanism by establishi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…This suggested that the evolution of H 2 was suppressed due to the increased local pH at the nanocavities and the competing C 2 H 4 formation reaction. 36 These trends demonstrated that the 10-cycle Cu foil accelerated C−C coupling rather than the formation of CH 4 during CO 2 RR, meaning that the nanocavities introduced by the CV treatment were beneficial to reduce CO 2 to C 2 H 4 and suppress the generation of CH 4 . This conclusion could be confirmed by the performance on the Cu foils treated with different CV cycles.…”
mentioning
confidence: 95%
“…This suggested that the evolution of H 2 was suppressed due to the increased local pH at the nanocavities and the competing C 2 H 4 formation reaction. 36 These trends demonstrated that the 10-cycle Cu foil accelerated C−C coupling rather than the formation of CH 4 during CO 2 RR, meaning that the nanocavities introduced by the CV treatment were beneficial to reduce CO 2 to C 2 H 4 and suppress the generation of CH 4 . This conclusion could be confirmed by the performance on the Cu foils treated with different CV cycles.…”
mentioning
confidence: 95%